Occurrence and spatial distribution of microplastics in beach sediments of Cox's Bazar, Bangladesh - Rahman, Shahriar Md Arifur; Robin, Gulam Saruar; Momotaj, Mahila; Uddin, Jamir; Siddique, Mohammad Abdul Momin (Marine pollution bulletin, 2020)
The present study is the first attempt to investigate the occurrence and distribution pattern of microplastics (MPs) in the beach sediments covering a 36 km long beach at Cox's Bazar, Bangladesh. Fourier-transform infrared spectroscopy was used to identify the MP particles (>300 μm). The mean abundance of plastics in this study site was 8.1 ± 2.9 particles kg-1. The abundance of MPs in the sediments was found in the following order: Fragments>Fibers>Foams>Beads>Films. The most abundant polymer types were Polypropylene (PP) (47%) and Polyethylene (PE) (23%). Most of the PP was atactic, while the low-density and high-density PE were in the balance. A higher abundance of MPs was observed in the wrack line compared to the other zones across the shore. The designated public tourist spots corresponding to few sampling sites showed significantly (P < 0.05) higher MPs than the sites with no tourist activity.
Keywords: Bangladéš; Plastic pollution; Water Pollutants, Chemical; Environmental Monitoring; geologické sedimenty; mikroplasty; Beach sediments; monitorování životního prostředí; Bangladesh; Polyethylene; Polypropylene; Tourism; Plastics; Microplastics; Geologic Sediments; chemické látky znečišťující vodu; plastické hmoty